Financial capital and startup survival - LEE, Jeongsik (Institutional Knowledge at Singapore Management University, 2011)
Are entrepreneurs liquidity-constrained? We attempt to answer this question by investigating the impact of financial capital on startup survival. The analysis of about 5,000 startups from the Kauffman Firm Survey data shows that, controlling for human capital, having some type of financial capital increases survival chances, supporting the existence of liquidity constraints. Interestingly, however, the effects are not uniform across types of capital: securing loans is associated with higher survival likelihood but receiving equity investments shortens startup longevity. Accounting for the endogeneity in financing using the Inverse Probability Treatment Weighted (IPTW) estimation reveals that the negative effect of equity capital is largely due to selection. Our findings highlight the heterogeneous effects across types of financial capital, each of which works through a different dynamic in influencing entrepreneurial performance such as survival.